2016
DOI: 10.17795/jjhr-33783
|View full text |Cite
|
Sign up to set email alerts
|

Survey of Complications of Peripheral Venous Catheterization at an Intensive Care Unit of (ICU) of Susa City

Abstract: Background: Peripheral catheters are the most common invasive procedures in patients, and have several therapeutic uses, yet result in infectious and non-infectious complications as well as problems such as pain and bruising, drug and fluid leakage out of the vessels, ecchymosis, hematoma, thrombosis, embolism, infection and phlebitis. Objectives: The aim of this study was to evaluate the complications of peripheral veins catheterization and some related factors at an intensive care unit (ICU) of Susa city. Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2018
2018
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 28 publications
0
2
1
Order By: Relevance
“…However the study finding is contradictory to the findings from other studies Singh [7] reported that phlebitis was higher if inserted in forearm 65.5%, followed by dorsum of hand 54.7% and wrist joint 53.3%. Whereas the finding is inconsistent with the findings from other studies Hedayatinejad, Yoong [15] [19] which showed that insertion site did not significantly influence so no significant correlation seen between the insertion site and phlebitis.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…However the study finding is contradictory to the findings from other studies Singh [7] reported that phlebitis was higher if inserted in forearm 65.5%, followed by dorsum of hand 54.7% and wrist joint 53.3%. Whereas the finding is inconsistent with the findings from other studies Hedayatinejad, Yoong [15] [19] which showed that insertion site did not significantly influence so no significant correlation seen between the insertion site and phlebitis.…”
Section: Discussioncontrasting
confidence: 99%
“…The present study shows there is no association between socio-demographic variables which included age, gender, marital education and educational level with severity score which include after complete interventions scores (8, 16, 24, 32, 40, 48 hours) of participants in both experimental groups. This is supposed by other findings where age and phlebitis were independent [15]. However, there are no more studies to support this finding.…”
Section: Association Of Socio-demographic Variables and Severity Scorementioning
confidence: 58%
See 1 more Smart Citation